La comparación estereotipada en griego moderno (PHRASIS | Rivista di studi fraseologici e paremiologici, 2017)
Phraseological studies about modern Greek are still extremely few. That is why we decided to present a panorama of the stereotyped comparison in modern Greek taking as a model the studies carried out on this linguistic phenomenon in the Spanish language. For this purpose we have set up a corpus of about 80 Greek stereotyped comparisons from written sources, mainly dictionaries of the language in use, as well as from oral sources. After that, we have analyzed them briefly in their La comparación estereotipada en griego moderno24 Carlos Alberto Crida Álvarez National and Kapodistrian University of Athens formal, semantic, sociocultural and pragmatic aspects. Finally, we have seen that there are great similarities between the stereotyped comparisons of modern Greek and Spanish, however with the exceptions and peculiarities of each language.
Keywords: Phraseology, stereotyped comparison.